1991
DOI: 10.1016/0378-1097(91)90053-d
|View full text |Cite
|
Sign up to set email alerts
|

Potentials of Shigella flexneri Y strain TSF21 as a candidate vaccine against shigellosis: safety, immunogenicity and protective efficacy in Bonnet monkeys

Abstract: Summary A thymine‐requiring and temperature‐sensitive mutant of Shigella flexneri Y was tested in Bonnet monkeys for safety, immunogenicity and protective efficacy. A dose of 1011 cells when fed orally mimicked natural infection in having invaded epithelial cells, but was otherwise clinically non‐reactogenic. Animals immunized with two oral doses, each dose consisting of 1 × 1011 mutant bacteria, were fully protected when challenged, with respect to the lack of any clinical symptoms or detectable histological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1994
1994
2004
2004

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Such strains should be capable of generating a protective immune response in the host directed against each of the serotype specific O-antigen structures. This lab has previously reported the serotype-conversion of the serotype Y S. flexneri candidate vaccine strain, Temperature sensitivity mutation has a high rate of reversion [155,156] S. flexneri Y SFL114 Insertional inactivation of aroD No symptoms in monkeys at 2-3 Â 10 10 CFU 100% protection in monkeys after four doses Some reversion of phenotype observed in laboratory conditions [157] S. flexneri Y SFL124 Deletion of aroD Very mild symptoms in some human volunteers at 2 Â 10 9 CFU and children at up to 1 Â 10 9 CFU 100% protection in monkeys after three doses of 1 Â 10 11 CFU Strain is advantageous as it can be converted to new serotypes [135,[158][159][160] S. flexneri 2aSFL1070 Deletion of aroD Mild symptoms in volunteers at 1 Â 10 7 -1 Â 10 8 CFU. Increased clinical symptoms at 1 Â 10 9 CFU About 85% protection in monkeys after 4 doses 1 Â 10 11 CFU Further attenuation may be necessary [133,161] S. flexneri 2a CVD1203…”
Section: Multiple-serotype Protection Strategiesmentioning
confidence: 99%
“…Such strains should be capable of generating a protective immune response in the host directed against each of the serotype specific O-antigen structures. This lab has previously reported the serotype-conversion of the serotype Y S. flexneri candidate vaccine strain, Temperature sensitivity mutation has a high rate of reversion [155,156] S. flexneri Y SFL114 Insertional inactivation of aroD No symptoms in monkeys at 2-3 Â 10 10 CFU 100% protection in monkeys after four doses Some reversion of phenotype observed in laboratory conditions [157] S. flexneri Y SFL124 Deletion of aroD Very mild symptoms in some human volunteers at 2 Â 10 9 CFU and children at up to 1 Â 10 9 CFU 100% protection in monkeys after three doses of 1 Â 10 11 CFU Strain is advantageous as it can be converted to new serotypes [135,[158][159][160] S. flexneri 2aSFL1070 Deletion of aroD Mild symptoms in volunteers at 1 Â 10 7 -1 Â 10 8 CFU. Increased clinical symptoms at 1 Â 10 9 CFU About 85% protection in monkeys after 4 doses 1 Â 10 11 CFU Further attenuation may be necessary [133,161] S. flexneri 2a CVD1203…”
Section: Multiple-serotype Protection Strategiesmentioning
confidence: 99%
“…The expectation appears to be reinforced by recent findings in which the wild-type thyA gene and genes related to pyrimidine biosynthesis are implicated as major virulenceassociated genes in some invasive bacterial pathogens such as Shigella (12) and Salmonella (9). Indeed, we have recently shown that thyA mutant of Shigella flexneri Y is highly attenuated in rabbits and monkeys and also provides solid immune protection against shigellosis after oral immunization (1,3). In order to examine the molecular change in the mutant thyA gene of S. flexneri Y strain TSF21 (1) we have cloned and sequenced the gene from the mutant and its parent using the PCR approach (2) with primers designed from the published sequence of the thyA gene of E. coli K-12 (5).…”
mentioning
confidence: 93%